Islamophobia in the Reporting of Siti Elina in Tempo.Co: A Critical Discourse Analysis Study - Santuso Santuso; Bambang Wibisono; Sukarno Sukarno (ITScience (Information Technology and Science), 2023)
The mass media constructs events into news. It is not uncommon for the mass media to create a phobia effect in society when constructing certain events. This study aims to describe, interpret, and reveal Tempo.co's strategies in promoting Islamophobia in reporting on Siti Elina, a woman who brandished a gun in front of Istana Merdeka. This is a critical qualitative research. The research data is in the form of diction suspected to contain elements of Islamophobia. The data source is news on the Tempo.co online media that aired from October 25-28, 2022, and five articles were selected. Data collection used the observation method with the free participant observation technique and note-taking technique. After the data was collected, it was analyzed using the theoretical framework of critical discourse analysis (CDA) model by Norman Fairclough. The results of this study indicate that (a) in the text analysis dimension, Tempo.co constructs Islamophobia towards Islamic clothing and attributes, Islamic organizations, Islamic teachings, and Islamic religious teachers; (b) in the discourse practice analysis dimension, Tempo.co marginalized the issue by reporting on Siti Elina's case in an unbalanced manner; (c) in the sociocultural analysis dimension, the Islamophobic discourse produced by Tempo.co cannot be separated from the political interests involved.